Fasting activates optineurin-mediated mitophagy in chondrocytes to protect against osteoarthritis - Min-Na Zhang; Ran Duan; Gui-Hong Chen; Mei-Jun Chen; Chun-Gu Hong; Xin Wang; Zhi-Lin Pang; Chun-Yuan Chen; Hua-Feng Liu; Da Zhong; Hui Xie; Wen-Bao Hu; et al. (Communications Biology)
Abstract Mitochondrial homeostasis plays a crucial role in the pathogenesis of osteoarthritis (OA), a chronic musculoskeletal disorder characterized by articular cartilage degeneration and chondrocyte apoptosis. However, molecular mechanisms underlying the association between mitophagy and OA remain unclear. Here, we aimed to investigate the role of the autophagy receptor protein optineurin (OPTN) in OA, and explore the effects of dietary intervention on OA symptoms and its relationship with OPTN-mediated mitophagy. Our findings showed the downregulation of OPTN in patients with OA. Using an Optn-knockout mouse model, we demonstrated that OPTN deficiency leads to impaired mitophagy, resulting in the accumulation of damaged mitochondria, increased production of reactive oxygen species, and chondrocyte apoptosis. Furthermore, fasting prevented OA progression by activating OPTN-mediated mitophagy and maintaining mitochondrial homeostasis in mice. The present study revealed a novel mechanism by which OPTN-mediated mitophagy influences chondrocytes and the OA phenotype in Optn-knockout mice, suggesting that OPTN-mediated mitophagy plays a crucial role in OA development and progression. This study provides new insights into the pathogenesis of OA and offers a potential avenue for the development of novel drugs targeting OPTN to mitigate OA progression.